Trouble Will Find You - Lexau, Joan M.; Chesworth, Michael (Boston, 1994)
When his parents promise that he can get a puppy if he can stay out of trouble for just one day, Desmond "Diz" Aster tries his best, but a burglar almost spoils his efforts.
Keywords: Dogs; Fiction; Criminals; Fiction